1997
DOI: 10.1103/physrevb.56.14374
|View full text |Cite
|
Sign up to set email alerts
|

Order-disorder phase-transformation kinetics inp-chloronitrobenzene studied by nuclear quadrupole resonance

Abstract: p-chloronitrobenzene crystallizes in the centrosymmetric space group P2 1 /c. Since the molecule does not possess an inversion point, the crystal exhibit orientational disorder. Recently, it was found that this compound has an ordered phase stable below 282.6 K. In the present work, we study the order-disorder phase transformation kinetic using nuclear quadrupole resonance. Isothermal transformation curves for nine different temperatures are analyzed following the theory developed by Cahn. In both the order-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Curves of isothermal transformation for three different temperatures were analyzed. It is well-known that the area under the NQR line shape is proportional to the number of the observed nuclei and its central frequency is typical of the crystalline phase; in this case it characterizes the hydration degree . In an isothermal experiment, the NQR line width does not change over time, then the line amplitude is proportional to the volume fraction transformed.…”
Section: Resultsmentioning
confidence: 99%
“…Curves of isothermal transformation for three different temperatures were analyzed. It is well-known that the area under the NQR line shape is proportional to the number of the observed nuclei and its central frequency is typical of the crystalline phase; in this case it characterizes the hydration degree . In an isothermal experiment, the NQR line width does not change over time, then the line amplitude is proportional to the volume fraction transformed.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, nuclear quadrupolar resonance (NQR) had also been used to investigate this disorder on a local scale, with somewhat contradictory results (Meriles et al, 1996(Meriles et al, , 1997Gonzá lez & Pusiol, 1996). In light of the limitations of the powder diffraction study and the uncertainties observed in the various NQR spectroscopy studies, the molecular disorder in p-ClNB has now been reinvestigated using multi-temperature single-crystal X-ray diffraction.…”
mentioning
confidence: 99%
“…The raw material was purchased from Aldrich Chemical Co. and was recrystallized and ®nely ground at room temperature using a mortar. In order to obtain a complete transformation to the ordered phase (Meriles, Pe  rez, Schu È rrer & Brunetti, 1997), $2 g of homogeneous powder were vacuum packed in glass¯asks and stored in a commercial freezer at 250 K for three months. Part of the powder was then scattered and gently compacted against a carved 2 cm wide dip in a glass sample holder of low atomic weight, supplied by Rigaku Co. As the ordered crystalline phase is only stable at temperatures below 282 K, the whole operation was performed inside a chamber at 276 K, so avoiding an involuntary partial transformation of the material.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the recent observation of a crystalline phase (Meriles et al, 1996) (without disorder) that was stable below room temperature becomes especially relevant: it allows a comparative study of the effects of partial disorder which, as far as we know, is unique in the family of benzene-derived organic compounds. Although the disordered phase can be easily quenched, the transformation takes place spontaneously between 240 and 260 K and generates a crystalline arrangement which is stable until 282 K. At this temperature, a ®rst-order phase transition causes the arrangement to become disordered again and this state continues, at high temperatures, until the compound fuses at 355 K. Unfortunately, the extreme slowness which characterizes the nucleation and growth of the ordered phase combined with the particular temperature range in which these processes take place (Meriles, Pe  rez, Schu È rrer & Brunetti, 1997) have, up to now, impeded the obtainment of single crystals in this phase and have delayed the de®nition of its structure. The recent analysis of the (low-frequency) Raman spectrum revealed that the symmetry of the arrangement should be either P2 1 or Pn and that the phase change not only implies an orientational re-ordering, but also a complete change of the crystalline structure (Meriles, Schneider et al, 1997).…”
Section: Introductionmentioning
confidence: 99%